Traditional Games to Form Children’s Characters In Dieng Plateau Banjarnegara Central Java Indonesia - Iwandana, Dody Tri; Sugiyanto, Sugiyanto; Hidayatullah, Furqon (Journal of Education, Health and Sport, 2018)
ABSTRACT Background: The world of children is the world of play. In the era of globalization with the advancement of technology, making children prefer to remain silent playing games through handphones, computers, or television, especially in urban areas. The Banjarnegara Plateau region which a culture and tradition are very strongly held and still traditional. The purpose of the research is to: 1) Know the physical activity of playing children in the Dieng Plateau; 2) Know the values contained in the games performed by children in the Dieng Plateau. Subject and Method: This research was carried out in the Dieng Plateau, Banjarnegara Central Java Province, Indonesia. This research is a qualitative research. The method of the research is Triangulation method. The data collection technique uses observation, interviews, and documentation. Result: The results showed physical activity of children in the Dieng Plateau Banjarnegara area was traditional play. A traditional games that can be found in the dieng plateau, namely: cublak-cublak suweng, stilts, jamuran, bentengan, jump rope, gobak sodor, mandahan, and many others. Conclusion: Traditional games are considered very goods for training children physically and mentally. Indirectly, children will be stimulated creativity, agility, intelligence, and the breadth of their insight and high togetherness through a traditional games.